ANALISIS TINGKAT PENGANGGURAN TERBUKA DI PROVINSI ACEH TAHUN 2015-2024 - Putri Gian Syahfitri; Yeni Rahmawati; Sri Ningsih (PT. Hasba Edukasi Mandiri, 2026)
This study aims to examine the trend of the open unemployment rate (TPT) in Aceh Province over the 2015–2024 period and to determine the factors contributing to its changes. The research adopts a quantitative approach with a descriptive design, utilizing secondary data sourced from the Central Statistics Agency (BPS). Data analysis is conducted using a time series approach and presented through tables and trend graphs processed with Microsoft Excel. The findings reveal that the open unemployment rate in Aceh generally shows a downward trend, although fluctuations still occur, particularly a rise in 2020 due to the COVID-19 pandemic. The subsequent decline indicates a gradual economic recovery along with improved labor absorption. However, the unemployment rate remains relatively high compared to the national average, suggesting structural problems within the labor market, including skill mismatch and limited job availability. The novelty of this study lies in its regional focus combined with a descriptive time series analysis that links economic conditions with labor market dynamics. The results imply that appropriate policy interventions are required, especially in enhancing workforce skills, expanding employment opportunities, and strengthening labor-intensive sectors to support sustainable economic growth and reduce unemployment.